INTERACTION AND ITS FAILURES: AN APPROACH THROUGH EMBARRASSMENT AND SHAME - Hélène MAIRE; Rawan CHARAFEDDINE; Jean-Baptiste VAN DER HENST (Studia Universitatis Babeș-Bolyai. Philosophia, 2022)
The present study is a theoretical and methodological proposal rooted in the field of social developmental psychology and describes three objectives. First, it aims to show how transgressive situations are conducive to study of social norms governing interactions. Second, the similarities and differences between two emotions, namely shame and embarrassment, are outlined in order to better understand how their respective measures can highlight social norms in interactions. Third, we illustrate our proposal to study social norms through emotional reactions by presenting an ongoing experiment, that examines how children may react to a power situation.